2003
DOI: 10.1067/mva.2003.22
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of severe morbidity and death after elective abdominal aortic aneurysmectomy in patients with chronic obstructive pulmonary disease

Abstract: Fewer prescribed inhalers, lower hematocrit, renal insufficiency, and coronary artery disease are preoperative factors associated with unfavorable outcomes after open elective surgical repair of AAA in patients with COPD. Intensive management of these factors may reduce the hazards of AAA operations in these patients. COPD alone should not be considered a deterrent to the surgical treatment of AAAs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
36
0
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(38 citation statements)
references
References 15 publications
1
36
0
1
Order By: Relevance
“…A recent study found that a low preoperative hematocrit was also a predictor of a poor postoperative outcome. 46 These observations may suggest that COPD patients are more sensitive to the effects of anemia, acute or chronic, by the preexisting tissue hypoxia. Nevertheless, it may be argued that the higher mortality was the result of greater blood loss during surgery, especially as both studies had patients who underwent surgery for upper-gastrointestinal bleeding 45 or abdominal aortic aneurysm.…”
Section: Morbidity and Mortalitymentioning
confidence: 86%
See 1 more Smart Citation
“…A recent study found that a low preoperative hematocrit was also a predictor of a poor postoperative outcome. 46 These observations may suggest that COPD patients are more sensitive to the effects of anemia, acute or chronic, by the preexisting tissue hypoxia. Nevertheless, it may be argued that the higher mortality was the result of greater blood loss during surgery, especially as both studies had patients who underwent surgery for upper-gastrointestinal bleeding 45 or abdominal aortic aneurysm.…”
Section: Morbidity and Mortalitymentioning
confidence: 86%
“…Older cells are most likely to become stiffer and to be unable to penetrate the tissue microcirculation, so these transfusions may provide useful volume expansion but may not increase oxygen delivery. Further research is warranted Two studies 45,46 in which anemic COPD patients had undergone surgery found that mortality was higher than in the non-COPD subgroups. A recent study found that a low preoperative hematocrit was also a predictor of a poor postoperative outcome.…”
Section: Morbidity and Mortalitymentioning
confidence: 99%
“…In one of these studies, mortality from gastrointestinal bleeding appeared to be higher in a cohort of 53 COPD patients, compared with bleeding controls without COPD (32% versus 10%, respectively; OR 4.3; 95% CI 1.22-1.48; p,0.01) and to COPD controls without bleeding (32% versus 11%, respectively; OR 3.7; p,0.02) [43]. In the other study, suboptimal management (fewer prescribed inhalers), preoperative renal insufficiency, coronary artery disease and reduced haematocrit (average 34% versus 39%), were significantly associated (p50.002) with an unfavourable outcome in COPD patients undergoing elective open abdominal aortic aneurysmectomy [44].…”
Section: Clinical Relevance Of Anaemia Of Copd Mortalitymentioning
confidence: 94%
“…In a small set of anaemic ventilator-dependent COPD patients, raising haemoglobin levels to >12 g·dL -1 seemed to improve patients enough to make ventilator weaning possible. A reduced haematocrit was found to be an independent predictor of poor outcomes in COPD patients following elective open abdominal aortic aneurysm resection [65].…”
Section: Anaemiamentioning
confidence: 99%